SAT0652-HPR CHRONIC DISEASE MANAGEMENT AND HEALTH TECHNOLOGY READINESS OF PATIENTS WITH SYSTEMIC SCLEROSIS IN SWITZERLAND – A CROSS-SECTIONAL STUDY. (2nd June 2020) - Kocher, A.; Simon, M.; Chizzolini, C.; Distler, O.; Dwyer, A. A.; Villiger, P.; Walker, U.; Nicca, D.
Abstract : Background: People living with systemic sclerosis (SSc) often lack access to coordinated, specialized care and self-management support from qualified healthcare professionals. Such gaps lead to significant unmet health needs and inability to get preventive services. The Chronic Care Model (CCM) has been used to guide disease management across a wide range of chronic conditions. The CCM often uses e-health technologies to address self-management problems, connect patients with clinicians and reduce patient travel requirements. Objectives: To evaluate current SSc care practice patterns and elicit patient health technology readiness to define relevant aspects and resources needed to improve SSc chronic disease management. Methods: We employed a cross-sectional survey using the 20-item Patient Assessment of Chronic Illness Care (PACIC) instrument to assess how aspects of SSc care align with key components of the CCM. 1 Six items drawn from the '5A' (ask, advise, agree, assist, and arrange) model of behavioural counselling were included (all 26 items scored on 5-point scale, 1=never to 5=always). Acceptance of health technology was evaluated by adapting and combining questionnaires from Vanhoof 2 and Halwas 3 . German and French speaking SSc patients (>18 years) were recruited from university/cantonal hospitals and the Swiss scleroderma patients' association. Participants completed anonymous paper/online questionnaires. Data were analysed descriptively. Results: Of 101 SSc patients, most were female (76%), spoke German (78%) and had a median age of 60 years (IQR: 50-68). Median disease duration was 8 years (IQR: 5-15), spanning a range of severity (31% limited SSc, 36% diffuse SSc, 3% overlap syndrome). One-quarter (25%) did not know their disease subset. The mean overall PACIC score was relatively low (2.91±0.95) indicating that care was 'never' to 'generally not' aligned with the CCM. Lowest mean subscale scores related to Follow-up/ Coordination (2.64±1.02), Goal setting (2.68±1.07) and Problem-solving/Contextual Counselling (2.94±1.22). The single items 'Given a copy of my treatment plan' (1.99±1.38) and 'Encouraged to attend programs in the community' (1.89±1.16) were given the lowest ratings. The '5A' summary score was 2.84±0.97. In terms of technology readiness, 43% completed the survey online. Most participants owned a smartphone (81%), laptop (63%) and/or desktop computer (46%). The overwhelming majority of patients (91%) reported using the Internet in the last year – primarily for communication (e.g. emails, text messages). Participants indicated relatively little experience with e-health applications and participating in SSc online forums or self-help groups. Conclusion: To improve chronic disease management of SSc patients in Switzerland, current care practices warrant reengineering taking CCM components into account. Specific unmet needs relate to self-management support, help patients set individualized goals, and coordinate continuous care. Web-based technologies incorporating user-centred design principles may be a reasonable option for improving care. References: [1]Glasgow, RE, et al. Development and validation of the Patient Assessment of Chronic Illness Care (PACIC). Med Care 2005; 43(5): 436-44 [2]Vanhoof, JM, et al. Technology Experience of Solid Organ Transplant Patients and Their Overall Willingness to Use Interactive Health Technology . J Nurs Scholarsh 2018; 50(2): 151-62 [3]Halwas, N, et al. eHealth literacy, Internet and eHealth service usage: a survey among cancer patients and their relatives . J Cancer Res Clin Oncol 2017; 143(11): 2291-99 Disclosure of Interests: Agnes Kocher Grant/research support from: Sandoz to support the development of an eLearning module for patients with rheumatic diseases., Michael Simon: None declared, Carlo Chizzolini Consultant of: Boehringer Ingelheim, Roche, Oliver Distler Grant/research support from: Grants/Research support from Actelion, Bayer, Boehringer Ingelheim, Competitive Drug Development International Ltd. and Mitsubishi Tanabe; he also holds the issued Patent on mir-29 for the treatment of systemic sclerosis (US8247389, EP2331143)., Consultant of: Consultancy fees from Actelion, Acceleron Pharma, AnaMar, Bayer, Baecon Discovery, Blade Therapeutics, Boehringer, CSL Behring, Catenion, ChemomAb, Curzion Pharmaceuticals, Ergonex, Galapagos NV, GSK, Glenmark Pharmaceuticals, Inventiva, Italfarmaco, iQvia, medac, Medscape, Mitsubishi Tanabe Pharma, MSD, Roche, Sanofi and UCB, Speakers bureau: Speaker fees from Actelion, Bayer, Boehringer Ingelheim, Medscape, Pfizer and Roche, Andrew A. Dwyer: None declared, Peter Villiger Consultant of: MSD, Abbvie, Roche, Pfizer, Sanofi, Speakers bureau: Roche, MSD, Pfizer, Ulrich Walker Grant/research support from: Ulrich Walker has received an unrestricted research grant from Abbvie, Consultant of: Ulrich Walker has act as a consultant for Abbvie, Actelion, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, MSD, Novartis, Pfizer, Phadia, Roche, Sandoz, Sanofi, and ThermoFisher, Paid instructor for: Abbvie, Novartis, and Roche, Speakers bureau: Abbvie, Actelion, Bristol-Myers Squibb, Celgene, MSD, Novartis, Pfizer, Phadia, Roche, Sandoz, and ThermoFisher, Dunja Nicca: None declared